EVALUASI FAKTOR KERUSAKAN MODUL SURYA DAN DAMPAKNYA TERHADAP KINERJA SISTEM PLTS 2 MWP SUMALATA GORONTALO - Rehan Mukmin; Yunita Djamalu; Arifin Matoka; Aswin (Program Vokasi-Universitas Negeri Gorontalo, 2026)
The performance of a solar power plant (SPP) is significantly influenced by the condition of the solar modules, which are the primary components in the energy conversion process. Damage to the modules can lead to a decrease in efficiency and disrupt the stability of the power generation system. This study aims to identify the types and characteristics of solar module damage, analyze the dominant contributing factors, and evaluate their impact on the performance of the 2 MWp Sumalata SPP system in North Gorontalo. The method used is quantitative descriptive analysis with a direct field inspection approach, supported by operational data in the form of the number of damaged modules and inverter power output. The research findings indicate that PV module damage is primarily caused by burnt modules and a combination of cracked and burnt modules, as well as the occurrence of hotspots due to environmental and technical factors. Based on the inspection summary for the January–December 2025 period, a total of 507 damaged modules were recorded, comprising 238 modules on Transformer 1 and 269 modules on Transformer 2; indications of performance degradation were also found in the form of low open-circuit voltage (Voc) values in some modules. The impact of the damage is evident in the reduction of inverter output power and the potential decrease in daily energy production. On December 2, 2025, with an irradiance of 6.80 kWh/m², inverter number 41, with 22 damaged modules, produced 17.942 kW of power, which was lower than inverters 35–40, which were in the range of 18.4–20.74 kW. These results indicate that solar panel damage directly impacts the overall performance of the PV system, particularly in terms of generation efficiency and power output stability.